Flood Management Based on The Potential Urban Catchments Case Study Padang City - Driptufany, Dwi Marsiska; Guvil, Quinoza; Syafriani, Desi; Arini, Dwi (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
The water catchment area also indirectly impacts on flood control for areas that are lower than it because rainwater does not fall to the lower areas but is absorbed as groundwater. Increased development of Padang City will be inversely proportional to the reduction in water catchment areas and become an area that is impermeable that makes rainwater stagnate on the surface and flood occurs. The development of remote sensing technology and geographic information systems has made it possible to study the spatial patterns of potential water catchment areas in a wide range, including mapping the potential of water catchment areas in Padang City. This study aims to analyze the condition of the availability of water catchment areas for controlling water management and flood disasters in Padang City based on data on spatial parameters such as rainfall data, slope, soil type maps, and land use obtained from Landsat 8 OLI imagery data. This study uses the scoring and overlay method with the Geographical Information System. The results show that the condition of the water catchment area in the western part of Padang City have been critical, reaching 18.29% of the total area of ​​Padang City, this is due to land use that has undergone a change of function. If the water infiltration condition worsens (critical), it gives more opportunities for flooding and inundation. Thus the areas with the potential for water absorption which are categorized as critical and very critical in the research location can be said to be areas that are potentially prone to flooding and inundation, because the ground surface is no longer able to absorb water. Monitoring the potential of water catchment areas is one form of flood mitigation efforts.